1993
DOI: 10.1111/j.1399-6576.1993.tb03601.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of experimental nerve block by combinations of local anesthetic agents

Abstract: The effects of bupivacaine-prilocaine and meperidine-lidocaine combinations (as compared with those of the agents used alone) on the duration of peripheral sensory nerve block were studied with the infraorbital nerve block model (IONB) in the rat, and those on motor block with spinal anesthesia (SA) in the mouse. The duration of bupivacaine-induced IONB was invariably prolonged when prilocaine was included in the solution. When included in 0.125% bupivacaine, 1.0% prilocaine had a slightly less pronounced enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Maurette et al (20) also found a synergistic effect when meperidine was used in combination with a local anesthetic. However, Hassan et al (15) suggested there might be an interaction or antagonism between local anesthetic receptor sites because of their finding that the duration of an infraorbital nerve block was significantly shortened when meperidine was combined with lidocaine. Two factors may account for a lower incidence of anesthetic efficacy with the combination lidocaine/meperidine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Maurette et al (20) also found a synergistic effect when meperidine was used in combination with a local anesthetic. However, Hassan et al (15) suggested there might be an interaction or antagonism between local anesthetic receptor sites because of their finding that the duration of an infraorbital nerve block was significantly shortened when meperidine was combined with lidocaine. Two factors may account for a lower incidence of anesthetic efficacy with the combination lidocaine/meperidine.…”
Section: Discussionmentioning
confidence: 97%
“…A number of clinical and experimental studies (10 -22) have shown that meperidine induces spinal anesthesia and blocks action potentials, providing segmental and sensory blocks comparable in effect to lidocaine. In medicine, it has been administered intrathecally (8,10,14,16,18), spinally (13,20), and as a saddle block (11), as well as locally for intravenous regional anesthesia (21), block (15), and infiltration (22) for the effects of analgesia, anesthesia, or both.…”
mentioning
confidence: 99%
“…In evaluating anesthetic success and the incidence of pulpal anesthesia ( Figures 2 through 7), it can be seen that generally the duration of pulpal anesthesia begins to decrease after about 15 minutes, which accounts for a great deal of the problem with anesthetic success. Hassan and colleagues 29 found that the duration of a block was significantly shortened when lidocaine was introduced into a solution of meperidine. They felt the decreased duration was caused by interaction or antagonism at drug receptors in the nerve membrane or at nonspecific binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…22 Clinically, meperidine has local anesthetic activity. A number of clinical and experimental studies [24][25][26][27][28][29][30][31][32][33][34][35][36] have shown that meperidine induces spinal anesthesia and blocks action potentials, providing segmental and sensory blocks comparable to those provided by lidocaine. In medicine, it has been administered intrathecally, 22,24,28,30,32 spinally, 27,34 and as a saddle block, 25 as well as locally for intravenous regional anesthesia, 35 block, 29 and infiltration 36 for the effects of analgesia, anesthesia, or both.…”
mentioning
confidence: 99%
“…Using mouse models, Hassan et al 35 found a reduced duration (less than 44%) of inferior orbital nerve block when lidocaine was added to meperidine compared to the nerve block with meperidine alone. On the other hand, mast cells are a potential important site for the histamine-dependent, peripheral actions of meperidine.…”
Section: Discussionmentioning
confidence: 99%